2017
DOI: 10.1098/rsos.170445
|View full text |Cite
|
Sign up to set email alerts
|

Correction to ‘The mountains of giants: an anthropometric survey of male youths in Bosnia and Herzegovina’

Abstract: In figure 2, the height in Široki Brijeg is listed as 185.3 cm. The correct value is 185.4 cm. The corrected figure is shown below.average male height (cm) ≥184.0

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
2
1
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 0 publications
2
3
1
Order By: Relevance
“…Our previous study dealing with the stature of young males in Bosnia and Herzegovina (BiH) (Grasgruber et al, 2017) confirmed older reports according to which the people from the Dinaric Alps are one of the tallest in the world. It is obvious that they cannot currently reach their genetic potential due to poverty and a relatively poor quality of their diet, but given the presence of these factors, their height is even more remarkable.…”
Section: Introductionsupporting
confidence: 85%
See 2 more Smart Citations
“…Our previous study dealing with the stature of young males in Bosnia and Herzegovina (BiH) (Grasgruber et al, 2017) confirmed older reports according to which the people from the Dinaric Alps are one of the tallest in the world. It is obvious that they cannot currently reach their genetic potential due to poverty and a relatively poor quality of their diet, but given the presence of these factors, their height is even more remarkable.…”
Section: Introductionsupporting
confidence: 85%
“…Even more importantly, our data cannot support the mean height of girls in Dalmatia, who reached 171.1 cm in Split (n=873)approximately 2 cm more than in the present study. As already mentioned (Grasgruber et al, 2017), Pineau et al collected at least some of their data in Herzegovina and Dalmatia via personal communication with the local physical education teachers, which could influence their results. Furthermore, the secular trend of youths in Tuzla schools was not negatively affected by the Bosnian war (1992)(1993)(1994)(1995) and continued at a relatively fast rate (Grasgruber et al, 2017;Hadžihalilović et al, 2006), so we do not suppose that height in other regions of BiH would decrease, especially considering the fact that boys measured during our survey in BiH were growing up after the end of the war.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is striking that we cannot again confirm the results by Pineau et al (2005) continued at a relatively fast rate (Grasgruber et al, 2017;Hadžihalilović et al, 2006), so we do not suppose that height in other regions of BiH would decrease, especially considering the fact that boys measured during our survey in BiH were growing up after the end of the war.…”
Section: Discussioncontrasting
confidence: 63%
“…As already mentioned above, these differences reached 5 cm (166-171 cm) [1992][1993][1994][1995] and continued at a relatively fast rate (Grasgruber et al, 2017;Hadžihalilović et al, 2006), so we do not suppose that height in other regions of BiH would decrease, especially considering the fact that boys measured during our survey in BiH were growing up after the end of the war.…”
Section: Discussionmentioning
confidence: 88%